Three-dimensional finite element analysis of the composite and compomer onlays in primary molars. Issue 10 (27th July 2019) - Kirzioglu, Zuhal; Ceyhan, Derya; Sengul, Fatih; Altun, Ayse Ceren
Abstract: Resin onlay restoration is an esthetic alternative technique used for restoring extensively damaged primary molars. Understanding the behavior of materials under repeated functional stress and how the stress is transmitted to the remaining tooth structure is important. The aim of this study was to compare stresses in primary molars restored with indirect composite and compomer onlay. 3D frame models of the right mandibular and maxillary primary molars and the alveolar bone were created using computerized tomography images of a six-year-old girl. The enamel and dentine layers above the cement layer were unified to generate onlay restoration, and composite and compomer were used as restorative materials. The vertical occlusal load (100 N) was applied to the teeth in the occlusal contact areas. The von Mises stress distributions and normal stress distributions of the y-axis (parallel to the long axis of tooth) were evaluated. The occlusal stress is transmitted to the cervical part of healthy teeth by spreading it through the enamel layer. The composite and compomer restorative materials exhibited similar stress distribution patterns. An indirect technique creates a structure similar to the original morphological form, and it allows restorations to distribute high occlusal stresses and to minimize possible breakages.